Minocycline exacerbates apoptotic neurodegeneration induced by the NMDA receptor antagonist MK-801 in the early postnatal mouse brain - Inta, Ioana; Vogt, Miriam A.; Mallien, Anne Stephanie; Bettendorf, Markus; Gass, Peter; Inta, Dragos (European archives of psychiatry and clinical neuroscience, 2016)
NMDA receptor (NMDAR) antagonists induce in perinatal rodent cortical apoptosis and protracted schizophrenia-like alterations ameliorated by antipsychotic treatment. The broad-spectrum antibiotic minocycline elicits antipsychotic and neuroprotective effects. Here we tested, if minocycline protects also against apoptosis triggered by the NMDAR antagonist MK-801 at postnatal day 7. Surprisingly, minocycline induced widespread cortical apoptosis and exacerbated MK-801-triggered cell death. In some areas such as the subiculum, the pro-apoptotic effect of minocycline was even more pronounced than that elicited by MK-801. These data reveal among antipsychotics unique pro-apoptotic properties of minocycline, raising concerns regarding consequences for brain development and the use in children.